Myxedema Coma in a Pediatric Patient with Down Syndrome - Divecha, Chhaya A.; Tullu, Milind S.; Deshmukh, Chandrahas T.; Karande, Sunil (Journal of Pediatric Intensive Care, 2020)
Myxedema coma due to severe/long standing hypothyroidism is a known fatal endocrine emergency but is rare in children and unreported in pediatric Down syndrome. It mimics other conditions in the emergency room, making the diagnosis challenging. We present a 10-year-old-male child with global developmental delay and Down syndrome phenotype, admitted for altered sensorium subsequent to a febrile illness. The presence of myxedematous changes on clinical examination, on a background of altered sensorium and hypothermia, led to suspicion of myxedema coma, confirmed by laboratory testing. Due to nonavailability of triiodothyronine (T3), thyroxine (T4) was administered through nasogastric tube after an endocrine consult. Despite initial recovery in terms of improved consciousness, the child ultimately succumbed to refractory shock and terminal ventricular tachycardia. Our case highlights the need to consider myxedema coma as a differential diagnosis for altered mental status in the emergency room and use of screening tools for effective selection of patients.
Keywords: altered mental status; Down syndrome; hypothyroidism; PICU; myxedema coma